DOI: 10.25148/etd.fi14061500
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of single-sex versus coed education on the mathematical reasoning ability, verbal reasoning ability, and self-concept of highschool girls

Abstract: Differential effects of single-sex versus coed education on the mathematical reasoning ability, verbal reasoning ability, and self-concept of highschool girls" (1996) This study explored the differential effects of single-sex versus coed education on the cognitive and affective development of young women in senior year of high school.The basic research question was: What are the differential effects of single-sex versus coed education on the development of mathematical reasoning ability, verbal reasoning abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…For example, in a longitudinal study by Sullivan, Joshi, and Leonard (2010), girls who attended single-sex schools achieved significantly more exam passes than their coeducational counterparts and were more likely to obtain a college degree, but the results were mitigated once school context (e.g., private vs. public) was controlled. These findings counter the results of earlier studies that did not find significant differences in achievement between girls at single-sex schools and their coeducational counterparts (Conway, 1996;Harker & Nash, 1997;Shmurak, 1998).…”
Section: Single-sex Education and Academic Engagementcontrasting
confidence: 98%
“…For example, in a longitudinal study by Sullivan, Joshi, and Leonard (2010), girls who attended single-sex schools achieved significantly more exam passes than their coeducational counterparts and were more likely to obtain a college degree, but the results were mitigated once school context (e.g., private vs. public) was controlled. These findings counter the results of earlier studies that did not find significant differences in achievement between girls at single-sex schools and their coeducational counterparts (Conway, 1996;Harker & Nash, 1997;Shmurak, 1998).…”
Section: Single-sex Education and Academic Engagementcontrasting
confidence: 98%
“…The second instrument was to measure students' attitude towards problem solving. The researcher adapted the student attitudes' instrument by Charles et al (1987) and Conway (1996). The Cronbach alpha value of 0.75 indicates that the instrument has appropriate internal consistency.…”
Section: Instrumentationmentioning
confidence: 99%
“…Other research, however, has not supported the notion that single-sex environments promote women's STEM-related achievement and orientation. For example, Conway (1996) reported no significant differences in mathematics achievement, as measured by SAT scores, when comparing students in Catholic single-sex and coeducational schools. Additionally, Shmurak (1998) reported that girls at coeducational schools actually took more science courses when compared to girls attending single-sex schools.…”
Section: Single-sex Education and Stem Preparationmentioning
confidence: 99%